Whole-Genome Sequencing and Analysis of the White-Rot Fungus Ceriporia lacerata Reveals Its Phylogenetic Status and the Genetic Basis of Lignocellulose Degradation and Terpenoid Synthesis - Mao, Zhitao; Yang, Ping; Liu, Huanhuan; Mao, Yufeng; Lei, Yu; Hou, Dongwei; Ma, Hongwu; Liao, Xiaoping; Jiang, Wenxia (Frontiers in Microbiology, 2022)
Ceriporia lacerata is an endophytic white-rot fungus that has lignocellulolytic and terpenoid-biosynthetic abilities. However, little is known about the genomic architecture of this fungus, even at the genus level. In this study, we present the first de novo genome assembly of C. lacerata (CGMCC No. 10485), based on PacBio long-read and Illumina short-read sequencing. The size of the C. lacerata genome is approximately 36 Mb (N50, 3.4 Mb). It encodes a total of 13,243 genes, with further functional analysis revealing that these genes are primarily involved in primary metabolism and host interactions in this strain’s saprophytic lifestyle. Phylogenetic analysis based on ITS demonstrated a primary evolutionary position for C. lacerata, while the phylogenetic analysis based on orthogroup inference and average nucleotide identity revealed high-resolution phylogenetic details in which Ceriporia, Phlebia, Phlebiopsis, and Phanerochaete belong to the same evolutionary clade within the order Polyporales. Annotation of carbohydrate-active enzymes across the genome yielded a total of 806 genes encoding enzymes that decompose lignocellulose, particularly ligninolytic enzymes, lytic polysaccharides monooxygenases, and enzymes involved in the biodegradation of aromatic components. These findings illustrate the strain’s adaptation to woody habitats, which requires the degradation of lignin and various polycyclic aromatic hydrocarbons. The terpenoid-production potential of C. lacerata was evaluated by comparing the genes of terpenoid biosynthetic pathways across nine Polyporales species. The shared genes highlight the major part of terpenoid synthesis pathways, especially the mevalonic acid pathway, as well as the main pathways of sesquiterpenoid, monoterpenoid, diterpenoid, and triterpenoid synthesis, while the strain-specific genes illustrate the distinct genetic factors determining the synthesis of structurally diverse terpenoids. This is the first genomic analysis of a species from this genus that we are aware of, and it will help advance functional genome research and resource development of this important fungus for applications in renewable energy, pharmaceuticals, and agriculture.